Isolation Of Metagenomic Dna From Mangroove Soil And Construction Of Cosmid Library - K.SIVASUBRAMANI; J.RAJESH SINGH; DR.S.JAYALAKSHMI (International Journal of Pharma and Bio Sciences, 2012)
Microorganisms present in the marine environment, can act as a good source of large number of biologically active molecules like antibiotics, anti cancer compounds, a wide range of enzymes etc. Screening for such organisms based on currently available culture based techniques is yielding only limited results because only around 2 percent of microorganisms present in marine environment are culturable. Metagenomics is a promising technique for the screening and isolation of biologically active molecules even from unculturables. Environmental mega-DNA(eDNA) was isolated from marine sediments. It represents DNA from both culturables and unculturables. Isolated mega-DNA was ligated with pWEB-TNC vector from Epicentre. It was cloned into the EPI100-T1R E.coli, to construct cosmid library of the mega-DNA. Library was screened for antibiotic producing clones and enzyme producing clones. Positive clones were separated from the library and studied in detail. Out of the positive clones clone ML3 was known to produce maximum amount of lipase